The Ivory throne : chronicles of the House of Travancore - Pillai, Manu S., 1990- (Noida, Uttar Pradesh, India : HarperCollins Publishers, India, 2015)
"In 1498, when Vasco da Gama set foot in Kerala looking for Christians and spices, he unleashed a wave of political fury that would topple local powers like a house of cards. The cosmopolitan fabric of a vibrant trading society with its Jewish and Arab merchants, Chinese pirate heroes and masterful Hindu Zamorins was ripped apart, heralding an age of violence and bloodshed. One prince, however, emerged triumphant from this descent into chaos. Shrewdly marrying Western arms to Eastern strategy, Martanda Varma consecrated the dominion of Travancore, destined to become one of the most dutiful pillars of the British Raj. What followed was two centuries of internecine conflict in one of India's premier princely states, culminating in a dynastic feud between two sisters battling to steer the fortunes of their house on the eve of Independence. Manu S. Pillai's retelling of this sprawling saga focuses on the remarkable life and work of Sethu Lakshmi Bayi, the last, and forgotten, queen of the House of Travancore. The supporting cast includes the flamboyant painter Raja Ravi Varma and his wrathful wife, scheming matriarchs of violent, profligate and sordid character, wifeswapping court favourites, vigilant English agents, quarrelling consorts and lustful kings. Extensively researched and vividly rendered, The Ivory Throne conjures up a dramatic world of political intrigues and factions, black magic and conspiracies, crafty ceremonies and splendorous temple treasures, all harnessed in a tragic contest for power and authority in the age of empire."--From source other than the Library of Congress
A painter prince -- The queen of the Kupakas -- Three consorts -- The second favourite -- Her highness the Maharajah -- A Christian minister -- Malice domestique -- Tea and troubles -- The Boudoir Dewan -- Black magic -- In letters of gold -- Mother and son -- La revanche -- A real little grande dame -- A palace coup -- The ultimate eclipse -- The villain of the piece -- Rivers of blood -- The reluctant princess -- Once I had a kingdom.
Includes bibliographical references (pages 557-662) and index.
Also issued as an e-book.
Keywords: Setu Lakshmi Bayi, -- Maharani of Travancore, -- 1895-1985.; Travancore (India) -- History; Travancore (India) -- Kings and rulers